Comparative study of DNA extraction methods from fresh and processed yellowfin tuna muscle tissue. (18th December 2017) - Piskata, Zora; Pospisilova, Eliska; Borilova, Gabriela
ABSTRACT: The most common techniques used to identify tuna species include methods based on the detection of specific DNA. The quality of species-specific DNA crucially affects the efficiency of amplification during the subsequent polymerase chain reaction (PCR). Detection of DNA in processed products can be adversely affected by DNA fragmentation during the processing steps and the use of ingredients that may inhibit the PCR reaction. In this study, several processing treatments applied to the muscle tissue of yellowfin tuna ( Thunnus albacares ) were evaluated. For DNA isolation three DNA extraction methods were compared. The concentration, purity, and amplificability of DNA were tested. The results revealed the variability among extraction procedures in terms of DNA quality and quantity in tuna muscle tissue processed under different processing technologies.